Le Coefficient de Biotope par Surface adapté sous l’angle des mutations spatiales des friches bruxelloises (Belgique) - Fiorella Quadu (VertigO)
This article suggests avenues for improving the Brussels biotope area factor tools in order to take into account during the urbanization of urban wastelands their main characteristics influencing the development of biodiversity and its evolution in space and the duration. The particular context of urban wastelands, a source of covetousness or even conflict that is sometimes difficult to reconcile and which can simultaneously shelter different semi-natural habitats, provides an interesting testing ground for CBS to assess its applicability in urbanization projects. The work is based on both a literature review and applied cases. The article makes it possible to identify potential weighting factors complementary to those assigned in the Brussels CBS tools. They are distinguished into so-called "major" factors essential to the development of the biodiversity of an urban wasteland (soil and water) and into so-called "minor" factors necessary to describe the state and elementary dynamics of the biodiversity of an urban wasteland (area, age, environment, management, land cover). It highlights the relative importance of the combinations of factors capable of simplifying the calculation of the CBS as well as the need to have reference values ​​and spatial units.